Nitrogen self-doped phenolic resin-based hard carbon microspheres as well as preparation method and application thereof
By introducing a nitrogen source at the source end of the phenolic resin, the preparation of nitrogen-doped phenolic resin-based hard carbon microspheres is solved, and the problems of insufficient electrochemical performance of hard carbon and complex production process are improved, and the electrochemical performance of sodium ion batteries is improved.
Patent Information
- Application Number
- CN202411599435.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The electrochemical performance of hard carbon, the negative electrode material of existing sodium ion battery, is insufficient and the production process is complex, resulting in uneven nitrogen doping.
By introducing a nitrogen source at the source end of the phenolic resin, a simplified production process is used to achieve uniform distribution of nitrogen elements and atomic doping, nitrogen self-doped phenolic resin-based hard carbon microspheres were prepared.
It improves the long cycle stability, rate performance and specific capacity of hard carbon microspheres, and has the prospect of industrial application.
Smart Images

Figure CN119430140A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials and devices, and in particular to nitrogen self-doped phenolic resin-based hard carbon microspheres, a preparation method and applications thereof. Background Art
[0002] In recent years, the imbalance between supply and demand has caused the global lithium ore prices to soar, which has greatly limited the application of lithium-ion batteries in large-scale energy storage. The development of new electrochemical energy storage systems is urgent. Sodium-ion batteries, which have a similar structure to lithium-ion batteries but lower costs, have attracted widespread attention. Although sodium-ion batteries have bright application prospects, the commercialization process has been tortuous, and the biggest difficulty lies in the selection of negative electrode materials. Among the negative electrode materials, hard carbon in amorphous carbon is considered to be a potential negative electrode material for sodium-ion batteries.
[0003] Hard carbon is a type of carbon that is difficult to graphitize even at temperatures above 2500°C. After high-temperature carbonization, the curved graphitized carbon layers in hard carbon are stacked and connected to form a highly twisted structure and present many nanopores. In addition, there are a large number of vacancies, edges and defect sites in the hard carbon structure. Due to the special structure of hard carbon, it is still challenging to integrate high capacity, high initial coulombic efficiency (ICE) and good durability. In the modification of hard carbon materials, heteroatom doping (such as N, P, S, etc.) is the most commonly reported effective strategy. Taking nitrogen doping as an example, it is also divided into self-doping using nitrogen-containing precursors, or introducing nitrogen sources from the outside. For example, Dong Xiaoqian of Hebei University of Geosciences used phenolic resin-based porous carbon, polyvinyl pyrrolidone and MnCo in Chinese patent CN117373839A. 2 O 4 Nanospheres were mixed and calcined to obtain N-doped phenolic resin-based porous carbon-supported manganese-cobalt composite materials; Xiao Wende of Shanghai Jiaotong University carbonized phenolic resin and melamine resin in Chinese patent CN116425140A to obtain nitrogen-doped hard carbon materials. However, introducing nitrogen source from outside and mixing it with phenolic resin will face the problem of uneven nitrogen doping, and the production process is relatively complicated.
[0004] Therefore, it is necessary to simplify the production process and improve the electrochemical properties of hard carbon microspheres. Summary of the invention
[0005] In view of the above-mentioned shortcomings, the present invention provides a nitrogen self-doped phenolic resin-based hard carbon microsphere, a preparation method and its application. The phenolic resin hard carbon of the present application introduces a nitrogen source from the resin source end, simplifies the production process, and realizes uniform distribution of nitrogen elements and atomic-level doping. The material is used in sodium ion batteries, has excellent long-cycle stability, good rate performance and high specific capacity, and has industrial application prospects.
[0006] In order to achieve the above object, the present invention provides a method for preparing nitrogen self-doped phenolic resin-based hard carbon microspheres, comprising the following steps:
[0007] S1, adding deionized water to an alkaline catalyst to adjust the pH to 8.5-9.5, adding phenol monomer thereto at room temperature to form a phenol suspension A; then dropping an aldehyde monomer solution into the phenol suspension A to obtain a suspension B; wherein the phenol monomer is aminophenol;
[0008] It should be noted that the formation of phenol oxide ions is favorable in an alkaline environment, thereby promoting the addition of phenol and aldehyde, and under milder alkaline conditions, the addition reaction is 5 times that of the condensation reaction.
[0009] It should be noted that the phenol monomer of the present application is aminophenol, and this type of monomer carries an amino group. Compared with a single phenolic hydroxyl group, the presence of an amino group can increase the addition active sites of phenol. In addition, after carbonization, N atoms still exist in the hard carbon phase, achieving atomic-level doping. The electron-rich nitrogen atoms can adjust the electrical conductivity of the hard carbon material, increase the transmission rate of electrons, and thus improve the rate performance of the sodium ion battery. Secondly, nitrogen doping can also change the structure and chemical properties of the hard carbon material. The presence of nitrogen atoms will affect the bending and folding of the carbon layer, increase the active sites of the sodium storage reaction, and improve the storage capacity of sodium ions.
[0010] S2, after the suspension B is reacted at a temperature T1 for a certain time t1, the aldehyde monomer solution is added dropwise thereto, and then the suspension B is reacted at a temperature T2 for a certain time t2 to obtain a phenolic resin oligomer with a certain molecular weight;
[0011] S3, placing the phenolic resin oligomer together with the reaction solution into a hydrothermal reactor, reacting at a temperature T3 for a certain time t3, and obtaining phenolic resin microspheres after solid-liquid separation;
[0012] S4. Carbonizing the phenolic resin microspheres in two steps in an inert atmosphere to obtain nitrogen self-doped phenolic resin-based hard carbon microspheres; wherein the two-step carbonization is sequentially performing low-temperature T4 carbonization and high-temperature T5 carbonization.
[0013] According to one aspect of the present invention, in step S1, the alkaline catalyst is NaOH, Na 2 CO 3 、Ba(OH) 2 or NH 3 ·H 2 O; the aldehyde monomer is one or more of formaldehyde, acetaldehyde, propionaldehyde, glutaraldehyde, and furfural; the aminophenol is one or more of p-aminophenol and m-aminophenol.
[0014] According to one aspect of the present invention, in step S1, the molar ratio of the phenol monomer to the aldehyde monomer is 1:3-4.
[0015] It should be noted that the phenol monomer has about 2 to 3 reaction sites. In the first step, the phenol monomer and formaldehyde add to form hydroxymethylphenol, and in the second step, formaldehyde and hydroxymethylphenol further add. When the formaldehyde content is higher than 50%, the reaction of formaldehyde and hydroxymethylphenol is easier than the reaction of formaldehyde and phenol. Therefore, controlling the speed and amount of formaldehyde addition in the first step can promote the phenolic resin to form a more uniform polyhydroxymethyl compound, providing a core for the subsequent extension of the phenolic resin carbon chain.
[0016] According to one aspect of the present invention, in step S1, the dropping speed of the aldehyde monomer solution is 4-6 mL / min.
[0017] According to one aspect of the present invention, in step S2, the temperature T1 is 20-30°C, and the time t1 is 30-60 min; the temperature T2 is 40-60°C, and the time t2 is 60-120 min.
[0018] It should be noted that the above temperature T1 is a low-temperature reaction, which together with the excess formaldehyde added in step S2 promotes the further growth of the polymethylol compound into linear or a small number of small branched resin molecules, preparing for subsequent high-temperature cross-linking to form an insoluble thermosetting resin.
[0019] According to one aspect of the present invention, in step S2, the molar ratio of the aldehyde monomer solution to the phenol monomer is 3-4:1; and the relative molecular weight of the phenolic resin oligomer is 300-1000 g / mol.
[0020] According to one aspect of the present invention, in step S3, the temperature T3 is 80-150° C., and the time t3 is 6-24 hours.
[0021] It should be noted that in step S3, the preferred solid-liquid separation method is centrifugation, with a rotation speed of 7000-9000 r / min. In addition to centrifugation, freeze-drying, filtration followed by drying, etc. can also be used.
[0022] According to one aspect of the present invention, in step S4, the low temperature T4 is 300-500°C, the high temperature T5 is 1000-1500°C, and the time for the two carbonization steps is 60-120 minutes.
[0023] It should be noted that the decomposition temperature of amino resin is between 300 and 400° C. In step S4, the low temperature treatment is introduced before the high temperature carbonization, which can greatly alleviate the rapid removal of small molecular structures such as amino groups at high temperatures and reduce the structural defects of the material.
[0024] It should be noted that, in step S4, the inert atmosphere is nitrogen or argon.
[0025] Based on the same inventive concept, the present invention also provides nitrogen self-doped phenolic resin-based hard carbon microspheres prepared by the above preparation method.
[0026] It should be noted that the nitrogen self-doped phenolic resin-based hard carbon microspheres are spherical, the diameter of the phenolic resin-based hard carbon microspheres is 2-5 μm, and the interlayer spacing d 002 0.375-0.390nm, I D / I G The average width of the graphite domain along the a-axis is between 1.10 and 1.60. a The nanostructured carbon microspheres are 12-20 nm, and nitrogen self-doping is achieved. The proportion of N atoms in the hard carbon microspheres is 0.5-1.5 wt%, and the reversible specific capacity is 330-360 mAh / g.
[0027] Based on the same inventive concept, the present invention also provides the nitrogen self-doped phenolic resin-based hard carbon microspheres prepared by the above preparation method or the use of the above nitrogen self-doped phenolic resin-based hard carbon microspheres in carbon negative electrode materials for sodium ion batteries.
[0028] Based on the same inventive concept, the present invention also provides an electrode material, including a conductive additive, a binder and the above-mentioned sodium ion battery carbon negative electrode material protecting the nitrogen self-doped phenolic resin-based hard carbon microspheres of the present application.
[0029] Beneficial effects of the present invention:
[0030] (1) The design of the resin synthesis step in the preparation method of the present application takes into account the priority of addition reaction and condensation reaction, adjusts the alkaline environment, the order and amount of aldehyde addition, etc., in order to form spherical resin particles of uniform size. In the resin carbonization process, two-step carbonization is adopted to minimize the removal of nitrogen atoms and reduce surface defects.
[0031] (2) The spherical structure of the phenolic resin-based hard carbon microsphere material of the present application is conducive to the embedding and extraction of sodium ions from all directions. In addition, the phenolic resin-based hard carbon microsphere material realizes nitrogen self-doping, and the presence of nitrogen atoms expands the interlayer spacing. In addition, as an electron-rich group, while adjusting the conductivity of the hard carbon material, it increases abundant sodium storage active sites and improves the storage capacity of hard carbon for sodium ions.
[0032] (3) The present application realizes nitrogen doping directly from the source. Compared with recombining the resin with the nitrogen source, this method not only simplifies the production process, but also achieves uniform doping of nitrogen at the atomic level. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a SEM image of the hard carbon material prepared in Example 1 of the present invention;
[0034] Figure 2The SEM images of the hard carbon materials prepared in the comparative examples of the present invention are shown in FIG. 1 ; wherein (a) is the SEM image of the hard carbon material of comparative example 1; and (b) is the SEM image of the hard carbon material of comparative example 2.
[0035] Figure 3 The EDS graph of the hard carbon material prepared in Example 1 of the present invention; wherein (a) is the EDS graph; (b) is the distribution of C atoms; (c) is the distribution of N atoms; (d) is the distribution of O atoms;
[0036] Figure 4 The XRD patterns of the hard carbon materials prepared in Examples 1 to 4 of the present invention;
[0037] Figure 5 The Raman graphs of the hard carbon materials prepared in Examples 1 to 4 of the present invention;
[0038] Figure 6 The constant current charge and discharge curve diagram of the sodium ion battery prepared from the hard carbon material of Examples 1 to 4 of the present invention;
[0039] Figure 7 This is a cycle performance diagram of the sodium ion battery prepared from the hard carbon material of Examples 1 to 4 of the present invention. DETAILED DESCRIPTION
[0040] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.
[0041] Example 1
[0042] This example first provides a method for preparing nitrogen self-doped phenolic resin-based hard carbon microspheres, comprising the following steps:
[0043] Add appropriate amount of NH 3 ·H 2O is added to deionized water (PH is 8.5), a total of 15 ml. Then, 3.2 g of m-aminophenol is added thereto, and while stirring, 10 ml of formaldehyde solution (37% formaldehyde solution: deionized water volume ratio of 3:2) is added to the phenol suspension at a drop rate of 5 mL / min. After the suspension is reacted at 25°C for 30 minutes, 5 ml of formaldehyde solution (37% formaldehyde solution: deionized water volume ratio of 2:3) is continued to be added thereto, and reacted at 40°C for 120 minutes to obtain a phenolic resin oligomer (relative molecular weight of about 500 g / mol); then, the phenolic resin oligomer A is placed in a hydrothermal reactor together with its reaction solution, and reacted at 100°C for 24 hours, and then solid-liquid separation is performed to obtain phenolic resin microspheres;
[0044] The phenolic resin microspheres are reacted in argon at 400° C. for 2 hours and at 1400° C. for 2 hours to obtain the nitrogen self-doped phenolic resin-based hard carbon microspheres.
[0045] Example 2
[0046] This example first provides a method for preparing nitrogen self-doped phenolic resin-based hard carbon microspheres, comprising the following steps:
[0047] Add appropriate amount of NH 3 ·H 2 O is added to deionized water (PH is 8.5), a total of 15 ml. Then 3.2 g of p-aminophenol is added thereto, and while stirring, 10 ml of formaldehyde solution (37% formaldehyde solution: deionized water volume ratio of 3:2) is added to the phenol suspension at a drop rate of 4 mL / min. After the suspension is reacted at 25°C for 30 minutes, 5 ml of formaldehyde solution (37% formaldehyde solution: deionized water volume ratio of 2:3) is continued to be added thereto, and reacted at 45°C for 120 minutes to obtain a phenolic resin oligomer (relative molecular weight of about 500 g / mol); then the phenolic resin oligomer is placed in a hydrothermal reactor together with its reaction solution, reacted at 120°C for 24 hours, and then solid-liquid separation is performed to obtain phenolic resin microspheres;
[0048] The phenolic resin microspheres are reacted in argon at 400° C. for 2 hours and at 1200° C. for 2 hours to obtain the nitrogen self-doped phenolic resin-based hard carbon microspheres.
[0049] Example 3
[0050] This example first provides a method for preparing nitrogen self-doped phenolic resin-based hard carbon microspheres, comprising the following steps:
[0051] Add appropriate amount of NH 3 ·H 2O is added to deionized water (PH is 8.5), a total of 15 ml. Then, 3.2 g of m-aminophenol is added thereto, and while stirring, 10 ml of formaldehyde solution (37% formaldehyde solution: deionized water volume ratio of 3:2) is added to the phenol suspension at a drop rate of 5 mL / min. After the suspension is reacted at 25°C for 30 minutes, 5 ml of formaldehyde solution (37% formaldehyde solution: deionized water volume ratio of 2:3) is continued to be added thereto, and the reaction is carried out at 40°C for 180 minutes to obtain a phenolic resin oligomer (relative molecular weight of about 500 g / mol); then the phenolic resin oligomer is placed in a hydrothermal reactor together with its reaction solution, and reacted at 120°C for 24 hours, and then solid-liquid separation is performed to obtain phenolic resin microspheres;
[0052] The phenolic resin microspheres are reacted in argon at 400° C. for 2 hours and at 1300° C. for 2 hours to obtain the nitrogen self-doped phenolic resin-based hard carbon microspheres.
[0053] Example 4
[0054] This example first provides a method for preparing nitrogen self-doped phenolic resin-based hard carbon microspheres, comprising the following steps:
[0055] This example first provides a method for preparing a hard carbon microsphere negative electrode material, comprising the following steps:
[0056] Add appropriate amount of NH 3 ·H 2 O is added to deionized water (PH is 8.5), a total of 15 ml. Then, 3.2 g of p-aminophenol is added thereto, and while stirring, 10 ml of formaldehyde solution (37% formaldehyde solution: deionized water volume ratio of 3:2) is added to the phenol suspension at a drop rate of 5 mL / min. After the suspension is reacted at 25°C for 30 minutes, 5 ml of formaldehyde solution (37% formaldehyde solution: deionized water volume ratio of 2:3) is continued to be added thereto, and reacted at 40°C for 180 minutes to obtain a phenolic resin oligomer (relative molecular weight of about 500 g / mol); then the phenolic resin oligomer is placed in a hydrothermal reactor together with its reaction solution, reacted at 120°C for 18 hours, and then solid-liquid separation is performed to obtain phenolic resin microspheres;
[0057] The phenolic resin microspheres are reacted in argon at 450° C. for 2 hours and at 1400° C. for 2 hours to obtain the nitrogen self-doped phenolic resin-based hard carbon microspheres.
[0058] Comparative Example 1
[0059] The difference between this comparative example and Example 1 is that 3.2 g of m-aminophenol and 15 ml of formaldehyde solution (37% formaldehyde solution: deionized water volume ratio 3:2) are added into ammonia water with a pH of 8.5 at one time. Other steps and parameters are the same as in Example 1.
[0060] Comparative Example 2 (without nitrogen addition)
[0061] The difference between this comparative example and Example 1 is that m-aminophenol is replaced by phenol. The other steps and parameters are the same as those in Example 1.
[0062] Structural characterization:
[0063] The hard carbon materials prepared in Example 1 and Comparative Examples 1-2 were analyzed by scanning electron microscope (SEM). The results are as follows: Figure 1-2 As shown by Figure 1 It can be seen that the hard carbon prepared by the preparation method of the present application is spherical, and the particle size distribution is uniform, mostly 2 to 5 um. Figure 2 (a) It can be seen that when aminophenol and formaldehyde are added to the alkaline catalyst at one time, the phenolic resin hard carbon balls are more adhered together. Figure 2 (b) It can be seen that the resin prepared from phenol monomer presents irregular blocks after carbonization, and the particles are relatively large. However, too large particles are not conducive to the diffusion and storage of sodium ions in them.
[0064] The hard carbon material prepared in Example 1 was subjected to EDS spectrum analysis, and the results are as follows: Figure 3 As shown by Figure 3 It can be seen that in the hard carbon material prepared in Example 1 of the present application, nitrogen atoms are evenly distributed in the hard carbon spheres.
[0065] The X-ray diffraction spectra (XRD) of the hard carbon materials prepared in Examples 1 to 4 are as follows: Figure 4 As shown, Figure 4 The middle curve has two broad peaks near 23.5° and 43°, which is a very typical hard carbon structure feature. From the Bragg equation 2dsinθ=nλ, we know that the carbon layer spacing d in hard carbon is 002 (0.37~0.39nm) is much larger than the graphite interlayer spacing (0.334nm), which is more conducive to the transmission of sodium ions with larger radius.
[0066] The Raman spectra of the hard carbon materials prepared in Examples 1 to 4 are as follows: Figure 5 As shown, by calculation, we can know that I D / I G Between 1.10 and 1.60, corresponding to the average width L of the graphite domain along the a-axis a At 12-20nm.
[0067] Performance characterization:
[0068] The hard carbon powder (i.e., hard carbon microspheres) prepared in Examples 1 to 4 and Comparative Examples 1-2 were mixed with the conductive agent Super P and PVDF in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) was added and stirred to form a slurry, and then the slurry was evenly coated on the current collector copper foil, and after being dried with air at 120°C, it was cut into a circular pole piece with a diameter of 12 mm. Under vacuum conditions, the pole piece was dried at 70°C for 12 hours and then transferred to a glove box for standby use. The battery was assembled in a glove box with an Ar atmosphere, with a metal sodium sheet as the counter electrode, and the electrolyte was 1M NaPF6 dissolved in (ethylene carbonate and diethyl carbonate <Example 1>, dimethyl ether <Example 2>, ethylene carbonate and diethyl carbonate <Example 3>, ethylene carbonate and diethyl carbonate <Example 4>, ethylene carbonate and diethyl carbonate <Comparative Example 1>, ethylene carbonate and diethyl carbonate <Comparative Example 2>), and assembled into a CR2025 button battery. Among them, ethylene carbonate and diethyl carbonate <Example 1> means that when the hard carbon material of Example 1 is made into a CR2025 button battery, the electrolyte is 1M NaPF 6 Soluble in ethylene carbonate and diethyl carbonate. Other similar descriptions apply in the same way.
[0069] The constant current charge and discharge mode was used to perform electrochemical activation at a current density of 30 mA / g, and the battery cycle charge and discharge performance test was performed at a current density of 150 mA / g. The discharge cut-off voltage was 0 V, and the charge cut-off voltage was 2.0 V.
[0070] The sodium ion battery (CR2025 button battery) prepared from the hard carbon material of Examples 1-4 was subjected to constant current charge and discharge, and its constant current charge and discharge curve is as follows: Figure 6 As shown by Figure 6It can be seen that the reversible specific capacity of the sodium ion battery prepared by the hard carbon material of Example 1 is 301.8 mAh / g, the first coulombic efficiency (ICE) is 71.5%, the platform area specific capacity is 188.7 mAh / g, and the platform area specific capacity accounts for 62.5%; the reversible specific capacity of the sodium ion battery prepared by the hard carbon material of Example 2 is 320.4 mAh / g, the first coulombic efficiency (ICE) is 72.1%, the platform area specific capacity is 202.2 mAh / g, and the platform area specific capacity accounts for 63.1 %; The reversible specific capacity of the sodium ion battery prepared from the hard carbon material of Example 3 is 320.9 mAh / g, the first coulombic efficiency (ICE) is 73.2%, the platform area specific capacity is 207.5 mAh / g, and the platform area specific capacity accounts for 64.7%; The reversible specific capacity of the sodium ion battery prepared from the hard carbon material of Example 4 is 332.6 mAh / g, the first coulombic efficiency (ICE) is 74.9%, the platform area specific capacity is 239.0 mAh / g, and the platform area specific capacity accounts for 71.9%. The sodium ion battery (CR2025 button battery) prepared from the hard carbon materials of the above-mentioned comparative examples 1-2 is subjected to constant current charge and discharge, and the results of the constant current charge and discharge test are shown in Table 1. It can be seen that the reversible specific capacity of the sodium ion battery prepared from the hard carbon material of comparative example 1 is 291.4 mAh / g, and the platform area specific capacity is 172.7 mAh / g. Comparing this performance with the electrochemical performance of the sodium ion battery prepared from the hard carbon material of Example 1, it can be seen that the order of adding phenolic aldehyde has a greater impact on the phenolic resin formed and even the final hard carbon. Meta-aminophenol is insoluble in room temperature water, which means that the contact of phenolic aldehyde is extremely uneven during the addition of meta-aminophenol and formaldehyde, which is bound to affect the addition condensation and molecular chain extension cross-linking of the phenolic resin in the subsequent process, and then affect the uniformity of the formation of phenolic resin balls. Therefore, after the resin balls are carbonized, the graphite domains inside the hard carbon are uneven, that is, the interlayer spacing of each graphite domain is different, which in turn affects the platform area sodium storage, resulting in a decrease in the sodium storage performance of the entire hard carbon. As can be seen from Table 1, the reversible specific capacity of the sodium ion battery prepared from the hard carbon material of Comparative Example 1 is only 283.4mAh / g, and the platform area specific capacity is only 118.2mAh / g. It shows that the ordered carbon layer of the phenolic resin formed after phenol replaces meta-aminophenol lacks the regulation of nitrogen atoms during the carbonization process, and the interlayer and closed pores formed are not the best sodium storage structure, so the platform area specific capacity and even the entire reversible specific capacity are greatly reduced.
[0071] Table 1:
[0072]
[0073] The sodium ion battery (CR2025 button battery) prepared above was subjected to a cycle stability test, and its stability test curve is as follows: Figure 7 As shown. Figure 7It can be seen that the sodium ion battery prepared by the hard carbon material of Example 1 has a reversible specific capacity of 271.4 mAh / g and a capacity retention rate of 91.9% after 100 charge and discharge experiments at a current density of 1.5 A / g, indicating that the hard carbon structure is stable and has good cycle stability; the sodium ion battery prepared by the hard carbon material of Example 2 has a reversible specific capacity of 287.1 mAh / g and a capacity retention rate of 92.8% after 100 charge and discharge experiments at a current density of 1.5 A / g, indicating that the hard carbon structure is stable and has good cycle stability. Better; the sodium ion battery prepared from the hard carbon material of Example 3 has a reversible specific capacity of 283.5 mAh / g and a capacity retention rate of 89.7% after 100 charge and discharge experiments at a current density of 1.5 A / g, which indicates that the hard carbon structure is stable and has good cycle stability; the sodium ion battery prepared from the hard carbon material of Example 4 has a reversible specific capacity of 298.5 mAh / g and a capacity retention rate of 92.5% after 100 charge and discharge experiments at a current density of 1.5 A / g, which indicates that the hard carbon structure is stable and has good cycle stability.
[0074] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A method for preparing nitrogen self-doped phenolic resin-based hard carbon microspheres, characterized in that: The following steps are involved: S1, adding deionized water to an alkaline catalyst to adjust the pH to 8.5-9.5, adding phenol monomer thereto at room temperature to form a phenol suspension A; then dropping an aldehyde monomer solution into the phenol suspension A to obtain a suspension B; wherein the phenol monomer is aminophenol; S2, after the suspension B is reacted at a temperature T1 for a certain time t1, the aldehyde monomer solution is added dropwise thereto, and then the suspension B is reacted at a temperature T2 for a certain time t2 to obtain a phenolic resin oligomer with a certain molecular weight; S3, placing the phenolic resin oligomer together with the reaction solution into a hydrothermal reactor, reacting at a temperature T3 for a certain time t3, and obtaining phenolic resin microspheres after solid-liquid separation; S4. Carbonizing the phenolic resin microspheres in two steps in an inert atmosphere to obtain nitrogen self-doped phenolic resin-based hard carbon microspheres; wherein the two-step carbonization is sequentially performing low-temperature T4 carbonization and high-temperature T5 carbonization.
2. The method for preparing nitrogen self-doped phenolic resin-based hard carbon microspheres according to claim 1, characterized in that: In step S1, the alkaline catalyst is one or more of NaOH, Na2CO3, Ba(OH)2 or NH3·H2O; the aldehyde monomer is one or more of formaldehyde, acetaldehyde, propionaldehyde, glutaraldehyde, furfural; and the aminophenol is one or more of p-aminophenol and m-aminophenol.
3. The method for preparing nitrogen self-doped phenolic resin-based hard carbon microspheres according to claim 1, characterized in that: In step S1, the molar ratio of the phenol monomer to the aldehyde monomer is 1:3-4.
4. The method for preparing nitrogen self-doped phenolic resin-based hard carbon microspheres according to claim 1, characterized in that: In step S1, the aldehyde monomer solution is added at a rate of 4-6 mL / min.
5. The method for preparing nitrogen self-doped phenolic resin-based hard carbon microspheres according to claim 1, characterized in that: In step S2, the temperature T1 is 20-30°C, and the time t1 is 30-60 minutes; the temperature T2 is 40-60°C, and the time t2 is 60-120 minutes.
6. The method for preparing nitrogen self-doped phenolic resin-based hard carbon microspheres according to claim 1, characterized in that: In step S2, the molar ratio of the aldehyde monomer solution to the phenol monomer is 3-4:1; and the relative molecular weight of the phenolic resin oligomer is 300-1000 g / mol.
7. The method for preparing nitrogen self-doped phenolic resin-based hard carbon microspheres according to claim 1, characterized in that: In step S3, the temperature T3 is 80-150°C, and the time t3 is 6-24h.
8. The method for preparing nitrogen self-doped phenolic resin-based hard carbon microspheres according to claim 1, characterized in that: In step S4, the low temperature T4 is 300-500°C, the high temperature T5 is 1000-1500°C, and the time for the two carbonization steps is 60-120 minutes.
9. Nitrogen self-doped phenolic resin-based hard carbon microspheres prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The N atoms in the hard carbon microspheres account for 0.5 to 1.5 wt %.
10. Use of the nitrogen self-doped phenolic resin-based hard carbon microspheres prepared by the preparation method according to any one of claims 1 to 8 or the nitrogen self-doped phenolic resin-based hard carbon microspheres according to claim 9 in carbon negative electrode materials for sodium ion batteries.
Citation Information
Patent Citations
Nitrogen-doped hard carbon material, preparation method thereof and application of nitrogen-doped hard carbon material in negative electrode of sodium-ion battery
CN116425140A
N-doped phenolic resin-based porous carbon-supported manganese-cobalt composite material as well as preparation method and application thereof
CN117373839A
Phenolic resin microspheres, porous carbon material microspheres as well as preparation method and application of phenolic resin microspheres and porous carbon material microspheres
CN115651143A
Dual-carbon confinement MoS2 nano composite material, preparation method thereof and application of nano composite material in sodium-ion battery
CN117254005A
Spherical hard carbon negative electrode material and preparation method thereof, negative electrode plate and sodium ion battery
CN117800317A
Cited By
Hard carbon material and preparation method thereof, electrode and battery
CN121449047A
Nitrogen-doped modified phenolic resin hard carbon material as well as preparation method and application thereof
CN121651336A